The relationship between professional quality of life and general health of postgraduates in a Tertiary Care Hospital - Pavani Narukurthi; Raghuram Macharapu; Pramod Kumar Reddy Mallepalli; Ravulapati Sateesh Babu (Archives of Mental Health, 2018)
Introduction: Professional quality of life (ProQOL) is the measure that everyone feels in relation to their work. Both the positive and negative aspects of doing a job, influence the ProQOL. The majority of people spend more time at work than they do anywhere else, doing anything else. Aims and Objectives: The aim of this research is to study the relationship between ProQOL and general health in the postgraduates of a tertiary care hospital. Methodology: This is a cross-sectional study, which is conducted at Mamata General Hospital in Khammam, Telangana during a 6-month period (2017). The tools used are the ProQOL questionnaire and general health questionnaire. Results: Statistical analysis needs to be done, and the results will be analyzed and presented later. Conclusion: The current study is carried out to support the findings between the ProQOL and general health among postgraduates at a tertiary care hospital.